Magnet Paket Wisata Dalam Menarik Kunjungan Wisatawan Asing Berkunjung Ke Yogyakarta - Erlangga Brahmanto (Media Wisata, 2015)
Tourism is inseparable from the role of the Travel Agent. The role of travel agents is vital due to the creativity of “ concocting “ tour packages offered by the travel agent that makes the magnetic allure of foreign tourists come to Yogyakarta. With more and more of her as a tourist destination has to offer and the more diverse types packagege tour at an economical price, then the scene of a race between a travel agent - travel agent in Yogyakarta to captivate foreign tourists to come to Yogyakarta.ASITA ( Association of Indonesian Tours And Travel ) is a forum All Indonesia Tour & Travel Yogyakarta chapter, noting that there is a trend of foreign tourists visit it depends on the package tours offered by travel agents. Offered more competitive prices which makes the competition between travel agents with one another. Many factors affect the motivation of an individual or a group of tourists who come to Yogyakarta.